Upaya Meningkatkan Perkembangan Bahasa dan Moral Anak Melalui Penggunaan Media Audio Visual Film Animasi (Penelitian Tindakan Kelas pada Anak Kelompok B TK Ar-Rahman Desa Cilengkrang Kecamatan Wado Kabupaten Sumedang) - Hani Fatul Awaliah; Riska Aprilianti (STAI Terpadu Yogyakarta, 2019)
This study aimed to (1) improving language development of children through visual audio media animation film, (2) improving moral development of children through visual audio animation film. Method that used by researcher is classroom action research in Group B TK Ar-Rahman Desa Cilengkrang Kecamatan Wedo Kabupaten Sumedang 2017/2018 with 15 subject. Research design that used is Kemmis and Mc Taggart model. Data is collected and than analized, reflect, by used analysis technic data qualitative and quantitative.Language development of children is increasingly, average of score all children for first condition up to 1,9 (40%), at the cycle I of ability is increasingly up to 2,6 (66,7%), at the cycle II of ability is increasingly up to 3,1 (86,7%). Moral development of children for the first condition had score average up to 2,3 (53,3%), at the cycle I up to 2,5 (73,3%), at the cycle II had an average score of all children up to 2,8 (86,7%). Conclusion of this research can showed about visual audio media animation film can increase language development and moral of children.